The influence of social media on child feeding practices and beliefs among Hispanic mothers: A mixed methods study. (January 2020) - Griauzde, Dina H.; Kieffer, Edith C.; Domoff, Sarah E.; Hess, Kristen; Feinstein, Susannah; Frank, Amy; Pike, Denise; Pesch, Megan H.
Abstract: Objectives: (1) To identify factors that influence child feeding practices and beliefs among Hispanic mothers in a low-income community; (2) to describe the use of social media, other internet websites, and text messaging among Hispanic mothers; and (3) to explore mothers' perceptions of social media and/or text messaging interventions to prevent childhood obesity. Methods: Mixed methods descriptive study with a sequential explanatory design. Hispanic mothers ( N  = 66) from Detroit, Michigan with children between 6 and 36 months of age completed surveys regarding their child feeding practices, the source (s) influencing these practices, and their use of social media, internet, and text messaging. During qualitative interviews ( N   =  19), we explored mothers' use of social media and internet websites to find child health information as well as mothers' perspectives on social media/internet/text messaging interventions to promote child health. Results: Most survey respondents were between the ages of 20 and 39 years. One-third of mothers breastfed their child for >6 months; 68% did not introduce solids until their child was older than 6 months. The majority (96%) owned a cellphone; 75% used social media at least once daily. Few mothers indicated that social media and other internet websites influenced their child feeding decisions. During qualitative interviews ( N  = 19), almost all mothers expressed interest in social media and/or text messaging as a tool to communicate information regarding child health and feeding. Conclusions: Hispanic mothers had high rates of social media use and most desired social media/internet/text messaging interventions to promote child health. Highlights: Among low-income Hispanic mothers, Women, Infants, and Children (WIC) and family members were the most common sources that influenced their child feeding practices and beliefs. Most mothers owned cellphones with text messaging capabilities and utilized social media sites. Many mothers used social media and/or other internet websites to find information that influenced their own behavioral health (e.g., diet, physical activity). Few mothers used social media and/or other internet websites to inform their child feeding practices. Most mothers expressed interest in social media/internet/text messaging interventions to help promote child health and prevent obesity.